Digital Mythmaking: The Rebirth of Archetypes in Postmodern Literature - Dr. Asha Verma; Dr. Dinesh Kumar Verma (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This paper explores the rebirth of archetypes in postmodern and digital literature, examining how mythic structures are reconfigured in contemporary narratives by authors such as Salman Rushdie, Jeanette Winterson, and Neil Gaiman. Grounded in myth criticism (Frye, Campbell, Barthes) and postmodern narrative theory, the study investigates how classical archetypes the hero, the trickster, the shapeshifter are transformed through intertextual play, narrative multiplicity, and multimedia adaptation. The analysis highlights the role of digital storytelling, hypertext, and participatory culture in reshaping mythic imagination and constructing new forms of collective memory. Findings suggest that, while mythic structures persist, they operate in fluid, networked, and interactive contexts, demonstrating that postmodern myth is both a site of cultural critique and a vehicle for imaginative engagement. The study contributes to understanding the dynamic interplay between tradition, technology, and narrative innovation in contemporary literature.
Keywords: Digital Mythmaking; Archetypes; Postmodern Literature; Myth Criticism; Hypertext; Intertextuality